PERLINDUNGAN HUKUM BAGI KORBAN PEMBELIAN MOTOR CURIAN - Raden Riyan Budi Setiawan; Widhi Cahyo Nugroho (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Criminal justice is expected to control crime, especially against perpetrators who are victims of purchasing stolen goods, which are special crimes regulated outside the Crime codes. Basedon in the above, attracted the attention of the authors to write a thesis entitled "Legal Protection for Victims of Stolen Motorbike Purchases." This study aims to determine the application of criminal law to criminal acts of legal protection for victims of stolen motorcycle purchases. Besides that, the author also conducts a literature study using various literature and legislation related to the issues discussed in this thesis. The results obtained in this study are legal protection for victims of purchasing stolen motorbikes based on legal facts. To resolve this case, protection for victims of criminal acts is provided through channels outside the Criminal Code. One way is to use the means of civil justice. In the Civil Code article 1365. Protection for victims of criminal acts cannot be fulfilled by the Criminal Code so the regulation uses other laws which of course have weaknesses, so the problem-solving in the new Criminal Code concept in this matter receives attention, especially among others the regulation regarding criminal imposition guidelines and the types of criminal sanctions that exist in Article 54 and Article 55 paragraph I. Article 54 of the Criminal Code concept explains that the purpose of punishment is to resolve conflicts and their prevention does not merely apply minimum sanctions to avoid imposing crimes that do not fulfill the sense of justice of the community/victims